2019
DOI: 10.1097/pas.0000000000001304
|View full text |Cite
|
Sign up to set email alerts
|

Novel Internationally Verified Method Reports Desmoplastic Reaction as the Most Significant Prognostic Feature For Disease-specific Survival in Stage II Colorectal Cancer

Abstract: Multiple histopathologic features have been reported as candidates for predicting aggressive stage II colorectal cancer (CRC). These include tumor budding (TB), poorly differentiated clusters (PDC), Crohn-like lymphoid reaction and desmoplastic reaction (DR) categorization. Although their individual prognostic significance has been established, their association with disease-specific survival (DSS) has not been compared in stage II CRC. This study aimed to evaluate and compare the prognostic value of the above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 37 publications
0
50
0
2
Order By: Relevance
“…A subsequent study by the same group found that only DST but not PDC or TB was significantly associated with DSS on multivariate analysis. 9 In contrast, Konishi et al found PDC grade to have greater discriminatory power between low and high grade with respect to RFS than TB or stroma. 4 However, when the analysis was restricted to pT3/4 cases, DST had the most favourable AIC value.…”
Section: Pdc In Relation To Other Invasive Front Prognostic Markersmentioning
confidence: 93%
See 4 more Smart Citations
“…A subsequent study by the same group found that only DST but not PDC or TB was significantly associated with DSS on multivariate analysis. 9 In contrast, Konishi et al found PDC grade to have greater discriminatory power between low and high grade with respect to RFS than TB or stroma. 4 However, when the analysis was restricted to pT3/4 cases, DST had the most favourable AIC value.…”
Section: Pdc In Relation To Other Invasive Front Prognostic Markersmentioning
confidence: 93%
“…2 More recently, they reported strong agreement for PDC grade between the current method evaluating all slides and a modified method in which only a single slide with the deepest invasion is assessed, with a kappa of 0.798. 9 If validated by other groups (and the association with clinical outcome holds), this modification may improve ease of assessment.…”
Section: Issues Relevant To Practice-readiness D E F I N I T I O N mentioning
confidence: 99%
See 3 more Smart Citations